Regulation of Adrenal Aldosterone Production by Serine Protease Prostasin. (2nd March 2010) - Ko, Takehiro; Kakizoe, Yutaka; Wakida, Naoki; Hayata, Manabu; Uchimura, Kohei; Shiraishi, Naoki; Miyoshi, Taku; Adachi, Masataka; Aritomi, Shizuka; Konda, Tomoyuki; Tomita, Kimio; Kitamura, Kenichiro
Abstract : A serine protease prostasin has been demonstrated to have a pivotal role in the activation of the epithelial sodium channel. Systemic administration of adenovirus carrying human prostasin gene in rats resulted in an increase in plasma prostasin and aldosterone levels. However, the mechanism by which the elevation of prostasin levels in the systemic circulation stimulated the plasma aldosterone levels remains unknown. Therefore, we examined if prostasin increases the aldosterone synthesis in a human adrenocortical cell line (H295R cells). Luciferase assay using CYP11B2 promoter revealed that prostasin significantly increased the transcriptional activity of CYP11B2. Prostasin significantly increased both CYP11B2 mRNA expression and aldosterone production in a dose-dependent manner. Surprisingly, treatment with camostat mesilate, a potent prostasin inhibitor, had no effect on the aldosterone synthesis by prostasin and also a protease-dead mutant of prostasin significantly stimulated the aldosterone production. A T-type/L-type calcium channel blocker and a protein kinase C (PKC) inhibitor significantly reduced the aldosterone synthesis by prostasin. Our findings suggest a stimulatory effect of prostasin on the aldosterone synthesis by adrenal gland through the nonproteolytic action and indicate a new role of prostasin in the systemic circulation.